2019
DOI: 10.1186/s12955-019-1103-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and health-related quality of life: a cross-sectional study of primary care patients with multi-morbidity

Abstract: Background Multi-morbidity in chronic long-term conditions is a major concern for health services. Self-management in concert with clinical care forms part of the effective management of multi-morbidity. Self-efficacy is a mechanism through which self-management can be achieved. Quality of life is adversely impacted by multi-morbidity but could be improved by effective self-management. This study examines the relationship between self-efficacy and quality of life in primary care patients with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 44 publications
11
78
0
1
Order By: Relevance
“…Low motivation is complex, but may be partly attributable to poor selfrated health and low perceived physical capability. 23 Patients with co-morbidities often have higher disease burden and lower levels of self-efficacy, 24 and self-efficacy is one of the strongest correlates of physical activity behaviour. 25 Despite low levels of motivation, most participants wanted to be more physically active and acknowledged the potential benefits of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Low motivation is complex, but may be partly attributable to poor selfrated health and low perceived physical capability. 23 Patients with co-morbidities often have higher disease burden and lower levels of self-efficacy, 24 and self-efficacy is one of the strongest correlates of physical activity behaviour. 25 Despite low levels of motivation, most participants wanted to be more physically active and acknowledged the potential benefits of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…New variables were created for presence of a physical health condition (inclusive of asthma, heart disease, cancer, diabetes and shortness of breath) and mental health condition (inclusive of PTSD, MDD, phobia, social phobia, Obsessive Compulsive Disorder, GAD, psychotic disorder, eating disorder and health anxiety). Research has shown that co-morbidity and multi-morbidity are associated with worse mental health and quality of life [65][66][67] and greater loneliness [68], as such, new variables were created for the number of physical health and mental health conditions that participants reported. New categorical variables were also created for scores meeting the clinical threshold for depression (scores of 10 or higher on the PHQ-9), anxiety (scores of 10 or higher on the GAD-7) and probable PTSD (scores of 34 or higher on the PCL-5).…”
Section: Defining Variablesmentioning
confidence: 99%
“…According to a systematic review conducted in 2011, approximately one-third of all adults worldwide have multiple chronic conditions (MCCs), defined as the presence of more than 1 chronic disease [1,2]. Various studies across multiple countries, such as Canada, the United Kingdom (UK), the United States (US) and the Netherlands, established the correlation of MCCs with lower self-efficacy, reduced quality of life, and vulnerability to depression and other psychological issues, as well as disability [3][4][5][6][7]. Individuals with MCCs were found to require more medical attention, including a higher number of visits to primary and specialist care.…”
Section: Introductionmentioning
confidence: 99%